If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying G(0) = 3x + 4 Reorder the terms for easier multiplication: 0G = 3x + 4 Anything times zero is zero. 0G = 3x + 4 Reorder the terms: 0 = 4 + 3x Solving 0 = 4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 0 + -3x = 4 + 3x + -3x Remove the zero: -3x = 4 + 3x + -3x Combine like terms: 3x + -3x = 0 -3x = 4 + 0 -3x = 4 Divide each side by '-3'. x = -1.333333333 Simplifying x = -1.333333333
| 54/m=6 | | y=-1/6x-3 | | a^5-5(a^4)+15lna+4=0 | | -11=-t+8 | | N/4=25/n | | 91-q=32 | | 4y+9=49 | | X/8=5/100 | | sin^3x=27cos^3x | | x/148=4/1 | | y=nx-5 | | 5a^2-5b^2= | | x/148=4:1 | | 62=7e^8t | | T=8u^2v | | 8a-5=131 | | 1/2:1/3=n:20 | | a^5-5(a^4)+15ln(a)+4=0 | | y=integral(2*x*exp(-0.5*x)) | | -6=14-1/3 | | -4-10n=16 | | -6=-4x-1/3 | | 7/11=15/n | | 2x-12=6x-8 | | 2=3.14d | | -3x-4=6x+8-17 | | 9r+10=145 | | -29=v-14 | | z/8=1/2 | | 2(x-4)=3x-(2x-12) | | 5a^2-20a-60= | | -4cos(x-(pi/3)) |